PLATELET INDICES FOR PREDICTING LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS B INFECTION - Shendy Sherly Soeliauwan; Darwati Muhadi; Mutmainnah Mutmainnah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Chronic Hepatitis B involves liver parenchymal destruction leading to fibrosis. Decreased serum thrombopoietin associated with liver cell failure is thought as the leading cause of thrombocytopenia. Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) describe platelet size and degree of variation in platelet size respectively. The researchers intended to investigate whether platelet count, MPV, and PDW were variables to determine the severity of liver fibrosis in chronic hepatitis B patients. An observational study was carried out at the Dr. Wahidin Sudirohusodo Hospital Makassar from January 2015 until December 2016. A total of 100 chronic hepatitis B patients with negative HBeAg who underwent Fibroscan and complete blood count test were included in this study. A total of 100 chronic hepatitis B patients comprising, 11 with severe liver fibrosis, 16 with moderate liver fibrosis, 46 with mild liver fibrosis, and 27 with normal liver. There were significant differences in platelet count and MPV among liver fibrosis groups with p-value <0.001 and 0.046 respectively. No significant difference was observed for PDW among liver fibrosis groups (p=0.131). This study showed that platelet count and MPV were significantly different among the normal group, mild liver fibrosis group, moderate liver fibrosis group and severe liver fibrosis group in chronic hepatitis B patients. The researchers recommend to carry out studies with larger samples in number and distributed more evenly.